2022
DOI: 10.1155/2022/5290189
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tensile Strength Difference with Variable Gravel Sizes on the Hydraulic Fracture Propagation in the Conglomerate Reservoir

Abstract: Conglomerate reservoir is a representative reservoir of unconventional oil and gas resources, and hydraulic fracturing is also used to increase its production. However, the tensile strength of conglomerates with different sizes is various, which has an important impact on the hydraulic fracture propagation in the conglomerate reservoir. To study the tensile strength difference caused by the size of conglomerate gravel, some Brazilian splitting tests were conducted. To find the influence of tensile strength dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Thus, research on the fracture propagation law of natural glutenite reservoirs need to be further conducted. In this paper, the glutenite reservoir in the Mahu sag was taken as the research object, and a Brazil fracturing test was conducted to measure the tensile strengths of conglomerate specimens with different gravel particle sizes and cementation degrees [14].…”
Section: Methodology 21 Rock Mechanical Parameters Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, research on the fracture propagation law of natural glutenite reservoirs need to be further conducted. In this paper, the glutenite reservoir in the Mahu sag was taken as the research object, and a Brazil fracturing test was conducted to measure the tensile strengths of conglomerate specimens with different gravel particle sizes and cementation degrees [14].…”
Section: Methodology 21 Rock Mechanical Parameters Testmentioning
confidence: 99%
“…In combination with CT scanning, it was found that the initiation fracture was at th edge of the fine gravel, which indicated that the small pressure drop during the initia fracturing stage corresponded to the fracture of the cementation interface of the gravels The fracture propagated at the edge of the fine gravel and frequently interacted with th gravel during the extension, as was reflected by the high frequency of pressure fluctua tions in the curve, indicating that the subsequent pressure fluctuation corresponded to fracture propagation at the interface of the small-grain gravel cement around the well which meant that multi-peak pressure was exerted at the beginning of the fracture prop agation stage. This phenomenon was caused by the positive correlation between the frac ture toughness of the gravel and the grain size [14]. After the fracture of the small-grain gravel around the well, the fracture tended to pass around the gravel with a more tortuou morphology, and the gravel had an influence on fracture roughness, resulting in decrease in local fracture width (the average width of the "gravel-penetrating" fractures was only the general width of the "gravel-bypassing" fractures).…”
Section: Mode 2: Over-peak Pressure Decreased Slightly-stable Extensi...mentioning
confidence: 99%
See 1 more Smart Citation